CORRELATION AND PATH CO-EFFICIENT ANALYSIS OF QUANTITATIVE TRAITS IN OKRA [ABELMOSCHUS ESCULENTUS (L.) MOENCH] - DEEPAK K. SARYAM; S. K. MITTRA; A. K. MEHTA; SUNIL PRAJAPATI; SATISH KADWEY (The Bioscan, 2015)
A field experiment of correlation and path analysis was undertaken in 60 genotypes (5 checks) of okra for fruit yield and its quantitative traits, this study assist in identifying the characters which mainly contributing to the fruit yield. Yield plant-1 had highly significant positive phenotypic correlation with viz., number of fruits plant-1 (0.803), fruit diameter (0.376), fruit length (0.349), number of seeds fruit-1 (0.316), days to maturity (0.301), fruit weight (0.274) leaf blade width (0.219),100 seed weight (0.219), flower diameter (0.154), fruiting span (0.152), petiole length (0.151), and stem diameter (0.150). Highly negative non-significant association was observed with incidence of YVMV (-0.389), days to 50 per cent flowering (-0.319) and node at first flower appears (-0.307) this correlation study indicated that close interrelationship between genotypic and phenotypic correlation co-efficient and magnitude of genotypic correlation were higher than their corresponding phenotypic correlation for most of the traits. Phenotypic path coefficient analysis revealed that traits viz., number of fruits plant-1(0.733) followed by number of seeds fruit-1 (0.165), number of branches plant-1(0.147), fruit diameter (0.133), fruit weight (0.097), days to maturity (0.058), fruiting span (0.056), 100 seed weight (0.055), stem diameter (0.027) and plant height (0.023) have positive and high direct effects with fruit yield per plant. Number of fruits plant-1, fruit diameter, fruit length, plant height, number of seeds fruit-1, days to maturity, fruit weight, and stem diameter indicating importance of these characters and can be strategically used to selection criteria to develop and improve high yielding okra varieties.